2022
DOI: 10.3389/fmicb.2021.696632
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Distinguishes Patients With Epilepsy From Healthy Individuals

Abstract: Objective: The gut microecosystem is the largest microecosystem in the human body and has been proven to be linked to neurological diseases. The main objective of this study was to characterize the fecal microbiome, investigate the differences between epilepsy patients and healthy controls, and evaluate the potential efficacy of the fecal microbiome as a diagnostic tool for epilepsy.Design: We collected 74 fecal samples from epilepsy patients (Eps, n = 24) and healthy controls (HCs, n = 50) in the First Affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(53 reference statements)
1
7
1
Order By: Relevance
“…Our study also showed that Escherichia/Shigella had the highest relative abundance in ED, but it did not play an important position in the association network. These results relatively differed from those of another study ( Cui et al, 2022 ). Our findings also suggested that intestinal microbiota, such as Bifidobacterium and Escherichia/Shigella , could be used as potential microbial markers to classify possible subtypes of epileptic diseases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study also showed that Escherichia/Shigella had the highest relative abundance in ED, but it did not play an important position in the association network. These results relatively differed from those of another study ( Cui et al, 2022 ). Our findings also suggested that intestinal microbiota, such as Bifidobacterium and Escherichia/Shigella , could be used as potential microbial markers to classify possible subtypes of epileptic diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…The gut–brain axis, which is the largest axis, has been recently shown to sense and react to dynamic ecosystem changes by converting microbiota-associated chemical cues from the environment into neuronal impulses, thus implicating a potential role of the gut microbiota in epileptogenesis ( Yue et al, 2022 ). More evidence indicates that gut dysfunction/disorder is closely associated with the onset of and susceptibility to epilepsy, and some specific intestinal flora can function as gut biomarkers ( Gong et al, 2020 ; Cui et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the role of eukaryotic and viral participation in the emergence of epilepsy, larger samples and additional research are required. Among the prokaryotes, at the phylum level, Proteobacteria and Actinobacteriota were notably increased in the patients with epilepsy compared with the controls, conforming to the findings of a recent study [32]. There were also obvious differences between the epilepsy and control groups at the genus and species level.…”
Section: Discussionsupporting
confidence: 89%
“…Unexpectedly, an intervention study discovered that autistic children who consumed gluten- and casein-restricted diets were better able to handle autism-related behavioral challenges and had higher Faecalibacterium levels than autistic children who consumed the control diet (Grimaldi et al 2018 ). Members of this genus were found to be more abundant in individuals with epilepsy, although there were no links with severity status (Valles-Colomer et al 2019 , Cui et al 2021 ).…”
Section: Faecalibacterium In Relation To Health and Diseasementioning
confidence: 99%